Biochemical and inhibition studies of glutamine synthetase from Leishmania donovani. (June 2017) - Kumar, Vinay; Yadav, Shailendra; Soumya, Neelagiri; Kumar, Rohit; Babu, Neerupudi Kishore; Singh, Sushma
Abstract: Leishmaniasis is a group of tropical diseases caused by protozoan parasites of the genus Leishmania . Leishmania donovani is a protozoan parasite that causes visceral leishmaniasis, a fatal disease if left untreated. Chemotherapy for leishmaniasis is problematic as the available drugs are toxic, costly and shows drug resistance, hence, there is a necessity to look out for the novel drug targets, chemical entities and vaccine. Glutamine synthetase (GS) catalyzes the synthesis of glutamine from glutamate and ammonia. In the present study, we have identified and characterized GS from L. donovani . The nucleotide sequence encoding putative glutamine synthetase like sequence from L. donovani ( Ld GS, LDBPK_060370) was cloned. A 43.5 kDa protein with 6X-His tag at the C-terminal end was obtained by overexpression of Ld GS in Escherichia coli BL21 (DE3) strain. Expression of native Ld GS in promastigotes and recombinant L. donovani glutamine synthetase (r Ld GS) was confirmed by western blot analysis. An increase in expression of GS was observed at different phases of growth of the parasite. Expression of Ld GS in promastigote and amastigote was confirmed by western blot analysis. Immunofluorescence studies of both the promastigote and amastigote stages of the parasite revealed the presence of Ld GS in cytoplasm. GS exists as a single copy gene in parasite genome. Kinetic analysis of GS enzyme revealed K m value of 26.3 ± 0.4 mM forl - glutamate and V max value of 2.15 ± 0.07 U mg −1 . Present study confirms the presence of glutamine synthetase in L. donovani and provides comprehensive overview of Ld GS for further validating it as a potential drug target. Highlights: Glutamine synthetase (GS) was cloned from Leishmania donovani and biochemically characterized. GS exists as single copy gene in parasite genome. GS is expressed in both promastigote and amastigote form of the parasite. GS is localized in cytoplasm in both forms of the parasite. GS may be a possible new drug target for Leishmaniasis.